Behavioural finance and dividend changes as predictors of future profitability: A literature review - Hasan, Fakhrul; Fahlevi, Mochammad (Journal of Economics and Business Letters, 2024)
This paper's primary goal is to present a significant element of the current dividend policy challenges from the perspective of behavioral finance. Given that dividend policy is one of the more contentious subjects in corporate finance, and because of this, scholars in the field have recently attempted to address the dividend policy conundrum by utilizing behavioral finance viewpoints. From the standpoint of behavioral finance, the study provides a general overview of the literature on dividend policy. This work offers a review of the literature. Together with behavioral components, it summarizes the main theoretical justifications for the dividend policy from the standpoint of behavioral finance.